Conformal metasurface-coated dielectric waveguides for highly confined broadband optical activity with simultaneous low-visibility and reduced crosstalk - Zhi Hao Jiang (Nature Portfolio, 2017)
Controlling all the optical properties of dielectric waveguides is a challenging task and often requires complicated core- and cladding designs. Here, Jiang et al. demonstrate that a thin metasurface coating can control several optical properties simultaneously over a broad frequency range.